Desenvolvimento de um dispositivo de liberação controlada de fármaco para tratamento coadjuvante de doença periodontal - Queiroz, Vanessa de Moura (2018)
Periodontal disease is an inflammatory condition, mainly due to the action of the bacteria present in the subgingival film that can cause, if not treated, progressive loss of dental support tissues. The present study describes the development of a drug delivery system of antimicrobial, from a film with biodegradable polymer base, with the purpose of being used as an adjunct to chronic periodontal treatment. Thermoplastic starch films were manufactured by gelatinization and casting with the incorporation of chlorhexidine after 48 h of stirring for particle formation in the film. Morphological characterizations were performed by MEV and AFM and showed an irregular surface with particles incorporated with chlorhexidine with different sizes dispersed in a starch matrix. The hardness and elasticity modules were determined by nanoindentation, proving satisfactory results for the insertion proposal in the periodontal pocket. Raman and FTIR tests determined the chemical composition of the films, and showed the presence of starch and chlorhexidine. The DRX, demonstrated that the films were amorphous. The release of the in vitro drug was observed for 21 days by UV-vis spectrophotometry, with a total of 0.19 g/L of Chlorhexidine released. The microbiological potential of the films was evaluated by the disk diffusion test in agar against important micro-organisms of periodontal disease, P. gingivalis, P. intermedia, P. nigrescens, and P. melaninogenica and obtaining good inhibition of growth in all cases.